The Caucasian Archaeology of the Holy Land: Armenian, Georgian and Albanian Communities Between the Fourth and Eleventh Centuries CE - Tseḥanovits, Yanah (Handbook of Oriental Studies. Section 1 the near and Middle East Ser, 2018)
Intro -- Contents -- Preface -- List of Figures -- List of Maps -- List of Tables -- List of Abbreviations -- Chapter 1 Introduction -- Chapter 2 The Literary Sources -- Chronicles -- Procopius: De Aedificiis -- Sebeos: The Armenian History -- Movses Khorenatsi: History -- Movses Daskhurantsi: History of the Caucasian Albanians -- Ecclesiastical Documents -- The Typikon of the Great Laura -- Commemoratorium -- Holy Land Descriptions -- Jerome, Epistle 46 to Marcella -- Itinerarium Placentini -- Anastas Vardapet: List of the Armenian Monasteries -- Pseudo-Elisaeus: On Transfiguration -- Hagiographies -- John Rufus: Vita Petre Iberi -- Cyril of Scythopolis: Vita Euthymii -- Cyril of Scythopolis: Vita Joannis Hesychastae -- Cyril of Scythopolis: Vita Sabae -- Cyril of Scythopolis: Vita Theodosii -- Theodore of Petra: Vita Theodosii -- John Moschus: Leimonarion -- Anastasius the Sinaite -- Arsenius: Life of David Garejeli -- Life of Hilarion the Iberian -- Giorgi Mtsire: Life of George the Hagiorite -- Life of Prochorus -- Chapter 3 The Archaeological Evidence -- The Armenian Community -- Architectural Remains -- Inscriptions -- The Georgian Community -- Architectural Remains -- Inscriptions -- Chapter 4 Manuscripts and Colophons -- Armenian Manuscripts -- Georgian Manuscripts -- Palestinian Scriptoria -- Sinaitic Scriptorium -- Albanian Manuscripts -- Chapter 5 Finds vs. Texts: Archaeology and Literary Sources -- Types of Institutions -- Rural Coenobia -- Xenodochia -- Cemeterial Church -- Identification of the Sites -- Study Cases -- Chapter 6 Caucasian Communities and the Holy Land: The Patterns of Interaction -- Interaction with the Church of Jerusalem: The Archaeological Evidence -- Architectural Characteristics -- 'Pots and People' -- Burial Customs -- Interaction with the Church of Jerusalem: The Epigraphic Evidence -- The Choice of Language